Morphometric Character of Puntius binotatus (Pisces: Cyprinidae) Fish as the Sungi River Conservation Base of Tabanan Regency Bali - Suryani S.A.M.Putri; I Wayan Arya; A.A.Sg.Putri Risa Andriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Puntius binotatus is a local fish whose population continues to decline because there is not much in cultivation. The introduction of this fish has a negative impact and affects species diversity. Introduced fish in common waters can threaten the presence of native fish due to the phenomenon of hybridization with endemic fish, habitat destruction, predation, and parasites. Invasive fish in rivers have the potential to urge endemic fish habitats so efforts are needed so that invasive fish do not cause local fish to go extinct. The purpose of this study was to study the Morphometric Character of Puntius binotatus (Pisces: Cyprinidae upstream, middle, and downstream of the river due to the process of adaptation to changes in the environment so that local species do not experience extinction because their habitat is disturbed. The difference in morphometric character in upstream, middle, and downstream is due to the adaptation process to environmental changes, namely water quality parameters that have exceeded the standard of quality standards upstream are temperature, ammonia pH, phosphate, and BOD5. In the middle of the parameters that exceed the standard of quality standards are temperature, pH, Ammonia, Phosphate, BOD5, and TSS and downstream, namely temperature, pH, Ammonia, phosphate, BOD5, COD, and TSS have exceeded the standard quality distribution of characters upstream, middle and downstream has a similarity of 75.6% which has similar shapes at all stations and has a close kinship by the form of four morphometric character clusters.